MULTIMEDIA INTERAKTIF SEBUAH TEROBOSAN PEMBELAJARAN PAKET B - Sudarmanto, Dwi; KS, Yetty Widya; Ekawati, Yuni (JIV-Jurnal Ilmiah Visi, 2006)
Due to a signicant increase of learning achievement using B Package using ICT it’s strongly recomended to use multimedia in teaching mathetmaticts. Information and communication technology (ICT), is developing so fast. Its development is not easy to predict. Now a days, ICT is utilized by almost all aspects of human life including education. The research conducted was regarding the use of ICT to teach math. It was how influential interactive media can be used to facilitate instructional program of B Package to teach mathematics. Rasearch findings indicate that there is significant increase in learning achievement of B Package program participants by using interactive multimedia. This article recommends, therefore, using ICT based instructions with variety of interactive multimedia.